Syncop Section Inspirasi Vokal Goreh Tapuk Galambuak Randai Minangkabau dalam Karya Komposisi Musik Karawitan - Wikal Husni; Asep Saepul Haris; Rafiloza Rafiloza; Muhammad Zulfahmi (Jurnal Musik Etnik Nusantara, 2021)
This musical composition, entitled Syncop Section, was inspired by the game Tapuak Galambuak, the traditional art of Randai in Minangkabau. Tapuak Galambuak is a very interesting game movement in Randai's energetic performance and serves as a transition from changing story segments in Randai art. The Tapuak Galambuak game has a musical movement, in which there is a Goreh vocal music system which is played in a syncopated game pattern with vocal syllables such as hep, tah, tih, has, intertwined with each other by clapping hands on galembong. The principle of the Tapuak Galambuak game has similarities with the rhythm of jazz music such as syncopation, improvisation and unison, so that it becomes a unique one if it is collaborated. Furthermore, the Syncop Section combines two different types of typical music (Tapuak Galambuak and Acid Jazz) but have the same playing principle. Acid Jazz is part of the Jazz music genre that combines several elements from other genres such as Funk, Disco, and Soul. Syncop Section's musical compositions are made using the popular music approach method in the Acid Jazz sub-genre using basic concepts and developments that give rise to a musical collaboration. This work is shown in audio visual form using the concept of Work From Home during the current pandemic. The form of application of this work is presented by means of audio-visual performances aimed at reaching a wider audience.